2009
DOI: 10.2478/v10045-009-0033-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Aflatoxin B1 Contamination in Pre- and Post-Harvest Maize Kernels, Food Products, Poultry and Livestock Feeds in Tamil Nadu, India

Abstract: Aflatoxins, a group of mycotoxins mainly produced by Aspergillus flavus and A. parasiticus, have adverse health effects on humans and livestock that ingest aflatoxin-contaminated food products and feeds. To secure the safety of food and feed, regular monitoring of aflatoxin levels is necessary. In order to understand the magnitude of aflatoxin contamination, a survey was conducted in different agro-ecological zones of Tamil Nadu, India and 242 samples consisting of pre-and post-harvest maize kernels, food prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…This indicates that the Bhutanese population is exposed to the carcinogenic toxins that are present in the daily diet. Similar studies performed in Thailand reported an occurrence of 38.9% 26 ; 27.1%, in Zhejiang Province, China 27 ; 24.3%, in Vietnam 28 ; 78.0%, in Nepal 29 ; and 61.3%, in India 30 . The presence of these aflatoxins is inevitable, as factors such as changes in temperature and water availability related to actual climate changes (increased temperature, heavy rainfalls and droughts) all modulate mold growth and the production of mycotoxins 31 .…”
Section: Discussionsupporting
confidence: 80%
“…This indicates that the Bhutanese population is exposed to the carcinogenic toxins that are present in the daily diet. Similar studies performed in Thailand reported an occurrence of 38.9% 26 ; 27.1%, in Zhejiang Province, China 27 ; 24.3%, in Vietnam 28 ; 78.0%, in Nepal 29 ; and 61.3%, in India 30 . The presence of these aflatoxins is inevitable, as factors such as changes in temperature and water availability related to actual climate changes (increased temperature, heavy rainfalls and droughts) all modulate mold growth and the production of mycotoxins 31 .…”
Section: Discussionsupporting
confidence: 80%
“…The primary and major disease associated with aflatoxin consumption is hepatocellular carcinoma (HCC) or liver cancer [22] . Aflatoxin B1 is found widely and in greater concentrations than other naturally occurring forms of AF throughout the world in foods such as maize, peanuts and peanut products, cottonseed and its extractions, and to some extent, chillies, peppers, and pistachionuts [23] . It is, contaminate both, animal and human feed, particularly by intermediate cereals.…”
Section: Aflatoxicosismentioning
confidence: 99%
“…In total, there were 405 recorded locations of aflatoxin outbreaks, with 151 locations in Asia, 150 locations in Africa, 87 locations in America, 12 locations in Italy, Europe, and 5 locations in Australia. Specifically, the locations of aflatoxin data were retrieved from the following academic papers: Kenya (Collins et al 2010;Lewis et al 2005;Mutegi et al 2012); Zambia (Kachapulula et al 2017); Ghana (Agbetiameh et al 2018); Ethiopia (Chala et al 2013;Chauhan et al 2016); Mali (Waliyar et al 2015); Democratic Republic of Congo (Kamika and Takoy 2011;Kamika and Tekere 2016); Malawi (Waliyar et al 2013); Nigeria (Bankole and Mabekoje 2004); Tanzania (Seetha et al 2017); Benin (Setamou et al 1997); Uganda (Kaaya et al 2006); the Philippines (Arim 2000;Arim 2003;Quitco 1991;Yamashita et al 1995); Indonesia (Ali et al 1998;Rahayu et al 2003;Yamashita et al 1995); Thailand (Siriacha et al 1988;Yamashita et al 1995); India (Kishore et al 2002;Sharma and Parisi 2017;Shinha 1990;Vijayasamundeeswari et al 2009); China (Daren 1989;Li et al 2001;Wu et al 2016;Zhang et al 2011); the USA (Horn et al 1995;Pettit et al 1971); Brazil (Atayde et al 2012;Gonçalez et al 2008;Moreno et al 200...…”
Section: 3global Geographic Distributions Of Aflatoxinmentioning
confidence: 99%